Comparison of Sequence Analysis and a Novel Discriminatory Real-Time PCR Assay for Detection and Quantification of Lamivudine-Resistant Hepatitis B Virus Strains - Wightman, Fiona (American Society for Microbiology, 2004)
We report a rapid and accurate real-time PCR-based method to quantify wild-type and lamivudine-resistant hepatitis B virus by using a common forward primer paired with different reverse primers. Excellent concordance was demonstrated between sequencing and the discriminatory real-time assay; however, a mixture of quasispecies was more frequently detected by discriminatory real-time PCR.